Advanced Thermal Performance Strategies for Air Conditioning Systems in Tropical Climates - Chaiyat, Nattaporn (Science and Technology: Developments and Applications Vol. 4, 2025)
This study presents a method for analyzing air conditioner efficiency using a thermal performance curve. Several enhancement techniques are reported, including the use of a drop-in refrigerant, ultrasonic waves, phase change materials (PCM), vapor compression heat pumps, waste heat recovery units, and wastewater recovery, all evaluated under Thailand's weather conditions. An R-32 drop-in refrigerant was tested in an R-410A air conditioner model. The R-32 unit demonstrated lower environmental impact and a higher cooling energy efficiency ratio (EER) compared to the R-410A unit. In addition, a commercial R-32 air conditioner was integrated with a 40-kHz ultrasonic generator, resulting in a 7.69% increase in the EER compared to the conventional R-32 unit. A phase change material of Rubitherm20 (RT-20) was used in both paraffin ball and plastic pack forms to cool the return air of the evaporator. This application led to reductions in power consumption of 7.85% and 5.78%, respectively. An R-123 vapor compression heat pump was integrated with the air conditioner at the condenser to capture and elevate rejected heat to a hot water temperature of 60-70°C. An R-290 heat pump unit was able to achieve a maximum water temperature of 57ºC when using a waste heat recovery unit with a spiral coil tank. An R-32 air conditioner of 3.517 kW produced 18.302 L/day of wastewater recovery, sufficient to supply 12 L for 22 cannabis plants. Overall, the most effective method to enhance air conditioner cooling capacity was the combination of the R-32 air conditioner and ultrasonic waves, achieving a 7.69% increase in cooling efficiency. These technical data were tested under Thailand's climate. Thus, the EERs of each technique will slightly differ from this work, corresponding to the shrouding conditions.